Predictors of Unsatisfactory Conventional Pap Smears - Sharma, Reetika (J Midlife Health, 2020)
OBJECTIVE: The objective of this study is to determine the clinical predictors of unsatisfactory Pap smears. METHODOLOGY: This was a case–control study done in a tertiary care institute. All unsatisfactory conventional pap (CP) smears between January 2015 and June 2017 were retrieved, and the slides were viewed. Clinical details were recorded from request forms and case files. Simple and multiple logistic regression analyses were used to identify the predictors of unsatisfactory CP smears. RESULTS: In this study, we have included 314 unsatisfactory Pap smears and 541 controls with satisfactory Pap smears. Clinical parameters such as older age and cervical erosion proved to be important predictors of unsatisfactory pap smears. The most common reason for unsatisfactory pap smears was due to a paucity of epithelial elements (66.6%), followed by obscuration of smear details by blood/inflammatory cells/mucus (9.9%) and air drying artifacts (4.4%). There were multiple reasons in 19.1% of cases with unsatisfactory pap smears. CONCLUSION: Our study shows that older age groups and cervical erosion are predictors of unsatisfactory pap smears. Incidence of unsatisfactory pap smears can be reduced by education and retraining of health-care workers and doctors.